Tìm x:
(2x/3 - 3) : (-10) = 5/3
(3/4 + x)3 = -27/8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
a.
$(25-2x)^3:5-3^2=4^2$
$(25-2x)^3:5=4^2+3^2=25$
$(25-2x)^3=25.5=5^3$
$\Rightarrow 25-2x=5$
$\Rightarrow 2x=20$
$\Rightarrow x=10$
b.
$2.3^x=10.3^{12}+8.27^4=10.3^{12}+8.3^{12}=18.3^{12}=2.3^{14}$
$\Rightarrow 3^x=3^{14}$
$\Rightarrow x=14$
a)
\(\text{( 25 – 2x )³ : 5 – 3^2 = 4^2}\)
\(\text{( 25 – 2x )³ : 5 – 9 = 16}\)
\(\text{( 25 – 2x )³ : 5 = 16 + 9}\)
\(\text{( 25 – 2x )³ : 5 = 25}\)
\(\text{( 25 – 2x )³ = 25 . 5}\)
\(\text{( 25 – 2x )³ = 125}\)
\(\text{( 25 – 2x )³ = 5³}\)
\(\text{25 – 2x = 5}\)
\(\text{2x = 25 – 5}\)
\(\text{2x = 20}\)
\(\text{x = 10}\)
\(\text{________________________________________}\)
b)
\(\text{2.3^x = 10.3^12 + 8.27^4}\)
\(\text{2.3^x = 10.3^12 + 8.(3^3)^4}\)
\(\text{2.3^x = 3^12 . (10+8)}\)
\(\text{2.3^x = 3^12 . 18}\)
\(\text{3^x = 3^12 . 18:2}\)
\(\text{3^x = 3^12 . 9}\)
\(\text{3^x = 3^12 . 3^2}\)
\(\text{3^x = 3^14}\)
\(\text{=> x=14}\)
a) Ta có: \(\dfrac{-3}{5}x+\dfrac{-7}{4}=\dfrac{3}{10}\)
\(\Leftrightarrow\dfrac{-3}{5}x=\dfrac{3}{10}+\dfrac{7}{4}=\dfrac{41}{20}\)
\(\Leftrightarrow x=\dfrac{41}{20}:\dfrac{-3}{5}=\dfrac{41}{20}\cdot\dfrac{-5}{3}\)
hay \(x=-\dfrac{41}{12}\)
Vậy: \(x=-\dfrac{41}{12}\)
\(1\)) \(5-\left(10-x\right)=7\)
\(10-x=5-7\)
\(10-x=-2\)
\(x=10-\left(-2\right)\)
\(x=12\)
\(2\)) \(-32-\left(x-5\right)=0\)
\(x-5=-32-0\)
\(x-5=-32\)
\(x=-32+5\)
\(x=-27\)
1) Tìm số nguyên x, biết :
a) 3x = 94/ 273
3x = 1/3
3x = 3-1
=> x = -1
b) 3x = 98 / 273 . 812
3x = 37.38
3x = 315
=> x = 15
c) 2x - 3 / 410 = 83
2x - 3 = 83.410
2x - 3 = 226
=> x - 3 = 26
=> x = 29
d) 22x - 3 / 410 = 83 . 165
22x - 3 / 410 = 269
22x - 3 = 269 . 410
22x - 3 = 289
=> 2x - 3 = 89
2x = 91
x = 91/2
e) 35 / 3x = 310
3x = 35 : 310
3x = 3-5
=> x = -5
a: x=3
b: \(2x-1=2\)
hay \(x=\dfrac{3}{2}\)
c: \(\Leftrightarrow\left[{}\begin{matrix}2x-3=3\\2x-3=-3\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=0\end{matrix}\right.\)
a) (7x - 11)3 = 25.52 + 200
=> (7x - 11)3 = 1000
=> (7x - 11)3 = 103
=> 7x - 11 = 10
=> 7x = 10 + 11
=> 7x = 21
=> x = 21 : 7
=> x = 3
b) x10 = 1x
=> x10 = 1
=> x10 = 110
=> x = 1
c) x10 = x
=> x10 - x = 0
=> x(x9 - 1) = 0
=> \(\orbr{\begin{cases}x=0\\x^9-1=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x^9=1\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
Vậy...
\(A=\frac{4^5.9^4-2.6^9}{2^{10}.3^8-6^8.20}\)
\(A=\frac{\left(2^2\right)^5.\left(3^2\right)^4-2.\left(2.3\right)^9}{2^{10}.3^8-\left(2.3\right)^8.2^2.5}\)
\(A=\frac{2^{10}.3^8-2^{10}.3^9}{2^{10}.3^8-2^{10}.3^8.5}\)
\(A=\frac{2^{10}.\left(3^8-3^9\right)}{2^{10}.3^8.\left(1-5\right)}=\frac{3^8-3^9}{3^8.\left(-4\right)}=\frac{3^8.\left(1-3\right)}{3^8.\left(-4\right)}=\frac{-2}{-4}=\frac{1}{2}\)
Vậy A = \(\frac{1}{2}\)
\(B=\frac{2^{19}.27^3+15.4^9.9^4}{6^9.2^{10}+12^{10}}\)
\(B=\frac{2^{19}.\left(3^3\right)^3+3.5.\left(2^2\right)^9.\left(3^2\right)^4}{\left(2.3\right)^9.2^{10}+\left(2^2.3\right)^{10}}\)
\(B=\frac{2^{19}.3^9+3.5.2^{18}.3^8}{2^9.3^9.2^{10}+2^{20}.3^{10}}\)
\(B=\frac{2^{19}.3^9+3^9.2^{18}.5}{2^{19}.3^9+2^{20}.3^{10}}\)
\(B=\frac{2^{18}.3^9.\left(2+5\right)}{2^{19}.3^9\left(1+2.3\right)}=\frac{7}{2.7}=\frac{1}{2}\)
Vậy B = \(\frac{1}{2}\)
Ở đâu đấy !
\(\left(\frac{2x}{3}-3\right):\left(-10\right)=\frac{5}{3}\)
=> \(\frac{2x}{3}-3=\frac{5}{3}.\left(-10\right)\)
=> \(\frac{2x}{3}-3=-\frac{50}{3}\)
=> \(\frac{2x}{3}=-\frac{50}{3}+3\)
=> \(\frac{2x}{3}=-\frac{41}{3}\)
=> 2x = -41
=> x = -41/2